BANK ACTIVIST WITH FOREIGN CAPITAL PARTICIPATION IN UZBEKISTAN - Bakayev Xurshid Mahmudovich (American Journals, 2024)
The banking system is an important component of the market infrastructure. Because banks provide the economy with financial resources, foreign economic communication financing, payment implementation and in the provision of various financial services to the population plays an important role.